Quality of life, resource use, and costs related to hip fracture in Estonia. Issue 8 (August 2016) - Jürisson, M.; Pisarev, H.; Kanis, J.; Borgström, F.; Svedbom, A.; Kallikorm, R.; Lember, M.; Uusküla, A.
Abstract Summary We assessed the impact of hip fracture on health-related quality of life (HRQoL) and costs in Estonia. The mean 18-month HRQoL loss in quality adjusted life years (QALY) was estimated at 0.31, and the average cumulative cost from a societal perspective was 8146 euros per hip fracture patient. Introduction The aim of this study is to estimate the impact of hip fracture on HRQoL, resource consumption, and cost over 18 months after the fracture among individuals aged over 50 in Estonia. Methods A cohort of 205 hip fracture patients ≥50 years was followed up for 18 months. HRQoL was estimated before fracture (recall), after fracture, and at 4, 12, and 18 months using the EQ-5D instrument. Health care utilization and costs were obtained from a public health insurance fund database; social, informal, and indirect costs were estimated using patient-reported data. Results Hip fracture resulted in the mean 18-month HRQoL loss of 0.31 QALYs. The mean 18-months cumulative cost of hip fracture from a societal perspective was estimated at 8146 (95 % CI 6236–10717) euros per patient. Most of the cost was related to health care (56 %) and informal care (33 %), while social care contributed only 5 %. Utilization of outpatient rehabilitation and nursing care was low (8 % of patients). Conclusions The impact of hip fracture on HRQoL and cost was substantial. Despite appropriate inpatient care, utilization of rehabilitation, nursing care, and social care were low and potentially insufficient to meet the needs of patients with low HRQoL. The shortfall may partially explain a remarkably high use of informal care.